MISKONSEPSI SISWA DALAM MENYELESAIKAN SOAL HIMPUNAN BERDASARKAN TAHAPAN MASON - Andy Dwi Melianti; Edy Yusmin; Asep Nursangaji (Jurnal AlphaEuclidEdu, 2020)
There are facts obtained through interviews and observations of students' answers that the VII grade students of SMP LKIA Pontianak are suspected of having misconceptions. Based on theses facts, the purpose of this research is to reveal the form of misconception based on Mason stages and the causes of the misconception. The subjects involved in this research were fifteen students. This research is a case study research with a descriptive method. Data collection tools used modified CRI diagnostic tests and interviews. Based on data analysis, the misconceptions experienced by students in completing set operations consisted of notation misconceptions, generalization and specialization. Researchers found out of the three forms of misconception, the most common is notation misconception. In the problem solving stage according to Mason consists of three stages, namely  entry, attack, and review, students who experience misconceptions in two stages, namely at the entry stage, students experience notation misconceptions and at the review stage, students experience misconceptions of notation, generalization, and specialization. Researchers found the causes of misconceptions consisted of three factors, namely students' associative thinking, incomplete / wrong reasoning, and wrong intuition. Researchers found out of the three forms of misconception, the most common is wrong intuition.            Keyword: Causes of Misconceptions, Mason Stages, Misconceptions